Pengaruh Pendidikan Kewirausahaan Dalam Menumbuhkan Minat Berwirausaha Mahasiswa - Agung Muhammad Nur; Aulia Jannah; M. Muflih Dermawan (Pusat Riset dan Inovasi Nasional, 2025)
To achieve an optimal entrepreneurship ratio of 4% of the total population, Indonesia needs 5.8 million new business owners. Many educational institutions are now integrating entrepreneurship education into their curriculum because of the need to develop future generations of entrepreneurs. These include the extent to which entrepreneurship influences student education, the correctness and efficacy of entrepreneurship teaching techniques, and the controversies surrounding the feasibility of teaching entrepreneurship. The aim of this research is to test whether entrepreneurship education influences students' ability to produce plans to start a business? Students in the entrepreneurship class were used as research subjects. In this research, one of the data analysis methods used in this research is the normality test using the paired t test to measure differences. Research findings show that students' aspirations for entrepreneurship do not differ significantly from each other. This requires more thorough research into how well in-house entrepreneurship education fosters students' entrepreneurial ambitions as well as evaluation of entrepreneurship class content, instructors, and delivery strategies.